2019
DOI: 10.1007/s42452-019-1395-2
|View full text |Cite
|
Sign up to set email alerts
|

Performance of plastic waste for soil improvement

Abstract: Recycling plastic waste from water bottles has become one of the main challenges worldwide. The aim of this study is to recycle empty plastic water bottles as reinforcing material for the improvement of sandy soil. The laboratory tests were performed on both natural and reinforced sands with different plastic waste percentages: 0, 0.5, 0.75 and 1.0 of the dry weight of sand at relative density states of 30% and 60%. Direct shear box and the California Bearing Ratio, CBR tests were performed to determine the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 12 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Additionally, the study demonstrated that including plastic waste improves flexible pavement properties, including the CBR value. Farah and Nalbantoglu's study [22] noted that blending sand with 0.50 % and 0.75 % plastic waste increased the peak and critical friction angles. Adding waste bottle plastic chips to the sand enhanced its shear strength.…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, the study demonstrated that including plastic waste improves flexible pavement properties, including the CBR value. Farah and Nalbantoglu's study [22] noted that blending sand with 0.50 % and 0.75 % plastic waste increased the peak and critical friction angles. Adding waste bottle plastic chips to the sand enhanced its shear strength.…”
Section: Discussionmentioning
confidence: 94%
“…A decrease in plastic limit of 8.02% is observed as plastic powder percentages increase from 0 to 1%, followed by a 40% increase in plastic limit up to the 1-4% range for plastic powder contents. This change in mixture consistency is due to the quality of the mixture composition [17], its ability to exchange cations, and the high amount of clay minerals in the mixtures.…”
Section: 12plastic Limitmentioning
confidence: 99%
“…Plastic consumption per capita in Ethiopia has increased by approximately 13.1 percent per year in recent years, rising from 0.6 kilograms in 2007 to 2.8 kilograms in 2018, and is expected to reach 3.8 kilograms in 2020. Use of plastic waste has already been tried by earlier researchers in many forms, Farah, and Nalbantoglu [26], discussed the performance of plastic waste for improving soil properties. Peddaiah, et al [27] tried using plastic waste in the form of strips and improving the soil characteristics.…”
Section: 13mentioning
confidence: 99%